Willingness, perceived barriers and motivators in adopting mobile applications for health-related interventions among older adults: a scoping review protocol - Suzana Shahar; Nurul Asilah Ahmad; Arimi Fitri Mat Ludin; Shahrul Azman Mohd Noah; Noorlaili Mohd Tohit (BMJ Open)
Introduction The world’s older population continues to grow at an unprecedented rate. An ageing population poses a great challenge to our healthcare system that requires new tool to tackle the complexity of health services as well as the increasing expenses. Mobile health applications (mHealth app) is seen to have the potential to address these challenges, alleviating burdens on the healthcare system and enhance the quality of life for older adults. Despite the numerous benefits of mHealth apps, relatively little is known about whether older adults perceive that these apps confer such benefits. Their perspectives towards the use of mobile applications for health-related purposes have also been little studied. Therefore, in this paper, we outline our scoping review protocol to systematically review literature specific to older adults’ willingness, perceived barriers and motivators towards the use of mobile applications to monitor and manage their health.Methods and analysis Arksey and O’Malley’s scoping review methodology framework will guide the conduct of this scoping review. The search strategy will involve electronic databases including PubMed, Excerpta Medica Database, Cumulative Index of Nursing and Allied Health Literature, Cochrane Library, Google Scholar and ScienceDirect, in addition to grey literature sources and hand-searching of reference lists. Two reviewers will independently screen all abstracts and full-text studies for inclusion. Data will be charted and sorted through an iterative process by the research team. The extracted data will undergo a descriptive analysis and simple quantitative analysis will be conducted using descriptive statistics. Engagement with relevant stakeholders will be carried out to gain more insights into our data from different perspectives.Ethics and dissemination Since the data used are from publicly available sources, this study does not require ethical approval. Results will be disseminated through academic journals, conferences and seminars. We anticipate that our findings will aid technology developers and health professionals working in the area of ageing and rehabilitation.